OPTIMALISASI PENANGANAN MUATAN UNTUK MENCEGAH KENAIKAN TEKANAN PADA TANGKI MUATAN DI KAPAL LPG/C GAS CATALINA - Kaharuddin; Rusman; Siti Zulaikah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to identify the causes and handling efforts of increasing tank pressure during the LPG loading process on board LPG/C Gas Catalina. The method used is descriptive qualitative through observation, interviews, and documentation, supported by the use of NVivo 12 Pro software for data analysis. The results show that the increase in tank pressure is caused by high cargo temperature, suboptimal performance of the cargo compressor, the influence of hot weather, as well as the lack of crew experience and monitoring. The handling efforts include conducting safety meetings, monitoring temperature and pressure regularly, optimizing equipment, and improving crew competence.